«Examination methods in cardiology: diagnostic potential, clinical interpretation, test control». Penza, POSTART, 2005; 249 pp. - I. P. Tatarchenko; N. V. Pozdnyakova; O. I. Morozova; V. A. Shevyreva (Кардиоваскулярная терапия и профилактика)
.